Nanofractionation Platform with Parallel Mass Spectrometry for Identification of CYP1A2 Inhibitors in Metabolic Mixtures. (March 2018) - Zietek, Barbara M.; Mladic, Marija; Bruyneel, Ben; Niessen, Wilfried M. A.; Honing, Maarten; Somsen, Govert W.; Kool, Jeroen
With early assessment of inhibitory properties of drug candidates and their circulating metabolites toward cytochrome P450 enzymes, drug attrition, especially later in the drug development process, can be decreased. Here we describe the development and validation of an at-line nanofractionation platform, which was applied for screening of CYP1A2 inhibitors in Phase I metabolic mixtures. With this platform, a metabolic mixture is separated by liquid chromatography (LC), followed by parallel nanofractionation on a microtiter well plate and mass spectrometry (MS) analysis. After solvent evaporation, all metabolites present in the nanofractionated mixture are assayed utilizing a fluorescence CYP1A2 inhibition bioassay performed on the plate. Next, a bioactivity chromatogram is constructed from the bioassay results. By peak shape and retention time correlation of the bioactivity peaks with the obtained MS data, CYP1A2-bioactive inhibiting metabolites can be identified. The method correctly evaluated the potency of five CYP1A2 inhibitors. Mixtures comprising potent inhibitors of CYP1A2 or in vitro–generated metabolites of ellipticine were evaluated for their inhibitory bioactivities. In both cases, good LC separation of all compounds was achieved and bioactivity data could be accurately correlated with the parallel recorded MS data. Generation and evaluation of Phase II metabolites of hydroxylated ellipticine was also pursued.